A Review of Host Finding by Mosquitoes - Abi, Ahmad Jan (Journal of Natural Sciences – Kabul University, 2023)
Mosquitoes are small insects, fossil of mosquitoes are about 50 million years old. All human and animals. Mosquitoes affect population by bites and by the transmission of diseases. Mosquitoes belong to family Culicidae. The most important genera are Anopheles, Culex an Aedes. There are several criteria to distinguish these genera. Mosquitos’ larvae and pupae live aquatically. In Mosquitoes only adult female suck blood, a blood meal for female mosquitoes is essential for maturation of the ovum. Mosquito host-finding can be divided into successive phases: activation, oriented flight to the host, alighting on the host, probing, imbibing, withdrawal and take off. Mosquitoes are nocturnal or crepuscular feeders with a wide host range. Host location is achieved using a range of olfactory and visual cues.